High‐Efficiency and Stable Perovskite Solar Cells Enabled by Halogen‐Free Cosolvent‐Processed Pyrazine‐Based Dopant‐Free Hole Transport Material - Chetan Lakshman; Hyerin Kim; Bo Hyeon Cho; Donghyun Song; Jeonghyeon Park; Young Yong Kim; Jinhwan Yoon; Sung‐Ho Jin (EcoMat)
ABSTRACT The complex molecular structures of electron donor (D)–acceptor (A) polymers provide a wealth of useful hints for producing high power conversion efficiency (PCE) as hole transport materials (HTMs) in perovskite solar cells (PVSCs). Given the recent improvements in PCE, various features are focused on altering the functionalities of HTMs. In this study, a pyrazine‐based acceptor is fused with two known donors benzodithiophene (BDT) and dithienobenzodithiophene (DTBDT) to synthesize two new D–A type polymers (NBD‐Pyz and NDT‐Pyz) to employ them as dopant‐free HTM in PVSCs. The insertion of pyrazine moiety downshifted the energy levels and enhanced coplanarity for both the HTMs. NBD‐Pyz can significantly lower the trap density and passivate the perovskite layer. More interestingly, the NBD‐Pyz HTM performs better than NDT‐Pyz, exhibiting higher hole mobility and better solubility in 2‐methyl anisole (2MA) and o‐xylene. Moreover, a 2MA/o‐xylene cosolvent‐processed dopant‐free polymeric NBD‐Pyz HTM‐based device achieved a champion PCE of 22.9%. Unlike NDT‐Pyz and Spiro‐OMeTAD‐based PVSCs, the unencapsulated NBD‐Pyz devices were more stable, retaining almost 90% of their initial efficiency after 1000 h. In addition, excellent thermal stability was demonstrated by the resulting PVSCs without encapsulation.